2016
DOI: 10.1080/00173134.2015.1108362
|View full text |Cite
|
Sign up to set email alerts
|

A combined light and scanning electron microscopy study

Abstract: The uppermost Eocene Florissant Formation, Rocky Mountains, Colorado, has yielded numerous insect, vertebrate, and plant fossils. Three previous comprehensive palynological studies investigated sections of lacustrine deposits of the Florissant Formation and documented the response of plant communities to volcanic eruptive phases but overall found little change in plant composition throughout the investigated sections. These studies reported up to 150 pollen and spore phenotypes. In the present paper we used a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 128 publications
(116 reference statements)
0
7
0
Order By: Relevance
“…Ephedra pollen was represented by three species, following characters documented by Steeves and Barghoorn (1959;Plate I, 1;Plate II, 20-27;Plate V, 20-22). The two medium-sized forms we clearly identified were the first-and second-order branch-furrowed pollen of E. nevadensis and the smooth-furrowed pollen of E. torreyana (Davis, 2001;Bolinder et al, 2016;Bouchal et al, 2016). These were accompanied by a third species differentiated from above-mentioned by its small size and distinctive sculpture, short axis, and first-and second-order branched furrows (Plate I, 1; Plate II, 24; Plate V, 22).…”
Section: Comparison Of the Four Oligocene Florasmentioning
confidence: 69%
See 2 more Smart Citations
“…Ephedra pollen was represented by three species, following characters documented by Steeves and Barghoorn (1959;Plate I, 1;Plate II, 20-27;Plate V, 20-22). The two medium-sized forms we clearly identified were the first-and second-order branch-furrowed pollen of E. nevadensis and the smooth-furrowed pollen of E. torreyana (Davis, 2001;Bolinder et al, 2016;Bouchal et al, 2016). These were accompanied by a third species differentiated from above-mentioned by its small size and distinctive sculpture, short axis, and first-and second-order branched furrows (Plate I, 1; Plate II, 24; Plate V, 22).…”
Section: Comparison Of the Four Oligocene Florasmentioning
confidence: 69%
“…4 Axelrod's identifications accepted by Wolfe and Schorn (1990). These are tantalizing records of some importance because unequivocal pollen of this highly derived family (Asteraceae) was present as rare elements at Florissant (Wingate and Nichols, 2001;Bouchal et al, 2016) as well as at all four of these Oligocene sites but are not characteristic of earlier Cenozoic floras of the United States.…”
Section: Comparison Of the Four Oligocene Florasmentioning
confidence: 94%
See 1 more Smart Citation
“…The earliest pollen records are from the Maastrichtian of Canada (Srivastava 1969) and the United States(Nichols 2002). From the Palaeogene, pollen of this family is more 146F.Grímsson et al often reported and is known from the Paleocene to Eocene of the United StatesBouchal et al 2016a), the Eocene of Central and East Asia(Wang & Zhao 1980;Hoorn et al 2012), and the Eocene of western Eurasia(Akkiraz et al 2006;Worobiec & Gedl 2018). From the Neogene onward Amaranthaceae pollen is very common in Eurasia (summarised byMuller 1981;Stuchlik et al 2009).…”
mentioning
confidence: 99%
“…Nevertheless, taxonomic control is typically poorer in LM than in SEM studies. As far as known, SEM studies of the same dispersed pollen flora reveal usually higher biodiversity and taxonomic resolution than LM studies (Grímsson & Zetter 2011; Grímsson et al 2011, 2015a, 2016; Bouchal et al 2016). Thus, it could be expected that a comprehensive SEM study of the dispersed pollen at Messel and Eckfeld would provide a large number of distinct taxa (genera, groups of genera).
Figure 17.
…”
Section: Discussionmentioning
confidence: 94%